Design and Development of an Information System for Recognition of Endangered Animals in Indonesia Based on Android Using the RAD Method - Hasibuan, M. Syahputra; Alda, Muhamad (UIN Sumatera Utara, 2025)
The Medan City Ministry of Religion Office is a state ministry that provides Rare animals are animals that are few in number and very rarely found. An animal is said to be rare if its population is decreasing rapidly and the number worldwide is less than 10,000. Natural factors or those influenced by human activities cause animals to become rare and endangered, for example low reproductive rates, insufficient types of food available, habitat destruction, or illegal hunting. From this, there are several problems that can be identified in the introduction of rare and endangered animals in Indonesia. Most people do not know or know about the rare and endangered animals in Indonesia. Apart from that, there is still very little digital media that provides informative and interactive information. This has resulted in a lack of public knowledge about rare and endangered animals. Therefore, the aim of this research is to build an Android-based information system to make it easier for the public to obtain information on endangered animals in Indonesia. The system development method used is the Rapid Application Development (RAD) method which consists of planning stages, design workshops and implementation. Meanwhile, the tool used by the author in creating information system designs visually is UML (Unified Modeling Language). This Android-based information system was built using Kodular tools and the Firebase database. With this information system, it is hoped that it can help the public obtain information regarding endangered animals in Indonesia easily and quickly via Android cellphones.